(untitled) - Halzen, Francis (New York, 1984)
This self-contained text describes breakthroughs in our understanding of the structure and interactions of elementary particles. It provides students of theoretical or experimental physics with the background material to grasp the significance of these developments.
TNL610
Keywords: Leptons (Vật lý hạt nhân),Leptons (Nuclear physics),Particles (nuclear physics),Các hạt (vật lý hạt nhân)